A development process proposal for the ERP5 system - De Carvalho, R. A. (2007)
Modeling ERP software means capturing the information necessary for supporting enterprise management. This modeling process goes down through different abstraction layers, from enterprise modeling to code generation. Thus ERP is the kind of system where enterprise engineering undoubtedly has, or should have, a strong influence. For the case of Free/Open Source ERP, the lack of proper modeling methods and tools can jeopardize the advantage brought by source code availability. Therefore, the aim of this paper is to present a development process proposal for the Open Source ERP5 system. The proposed development process aims to cover different abstraction levels, taking into account well established standards and common practices, as well as platform issues. Its main goal is to provide an adaptable meta-process to ERP5 adopters. © 2006 IEEE.